Nonlinear oscillators under delay control - Dao, Nguyen Van (Vietnam Journal of Mechanics, 2000)
In this paper, oscillations and stability of nonlinear oscillators with time delay are studied by means of the asymptotic method of nonlinear mechanics. Harmonic, super harmonic, subharmonic and parametric resonances of a Duffing’s oscillator are analyzed. Analytical method in combination with a computer is used.